Implicit intervention approach for empathy: exploring the combined effects of empathic concern and visual perspective-taking - Taesun Kim; HeungSik Yoon; Sang Hee Kim (Frontiers in Psychiatry)
Interest in fostering empathy has expanded rapidly recently, with increasing recognition of its role in emotional wellbeing and positive social outcomes. The current study investigated whether interventions to enhance empathic concern and visual perspective taking would influence socioemotional information processing and enhance empathic responses toward others. For this purpose, we devised two implicit intervention tasks: the gamified implicit compassion promotion task (gam-iCPT) to target empathic concern, and the other-oriented visual perspective-taking task (OVPT) to target visual perspective taking. A total of 128 healthy adults were randomly assigned to one of four intervention groups: the combined, single gam-iCPT, single OVPT and control group. Intervention outcomes were assessed using the dot-probe attention bias task with facial expressions of emotions and the empathy rating task featuring distressed others. We found consistent differences in outcome measures between the combined intervention group and the single gam-iCPT group. Specifically, the combined group showed faster disengagement from emotional faces, as well as greater empathic concern and increased helping intentions toward sad victims, compared to the single gam-iCPT group. However, no significant intervention effects were observed when compared to the control group. These results suggest that implicit interventions to target both empathic concern and visual perspective taking together may have a potential impact on empathy-related socioemotional processing compared to targeting each single element. The absence of significant effects relative to the control group, however, highlight the complexity of mechanisms underlying empathy enhancement, warranting further investigations.